Boosting Business Performance: The Impact of Entrepreneurial Culture on Women Entrepreneurs’ Behavior - Qamariah, Inneke; Fadli, Fadli; Astuti, Windi; Nasution, Muhammad Dharma Tuah Putra (International Review of Management and Marketing, 2024)
Entrepreneurship has been extensively examined across various management disciplines, with significant attention given to women entrepreneurship, which has made considerable strides in recent years. Despite this positive trend, many women continue to face challenges in balancing their business responsibilities with household duties. These challenges often lead to role conflicts as women navigate the demands of both their professional and domestic roles. This research aims to evaluate the impact of adopting an entrepreneurial culture on shaping the entrepreneurial behavior of women entrepreneurs, with the ultimate goal of enhancing their business performance. The study involved 88 married women entrepreneurs and utilized partial least squares structural equation modeling (PLS-SEM) for analysis. Additionally, Importance-Performance Map Analysis (IPMA) was employed to elucidate the significance and impact of each variable. The findings highlight the crucial role of adopting an entrepreneurial culture in women entrepreneurship, demonstrating its substantial influence on both the transformation of entrepreneurial behavior and the enhancement of business performance. Consequently, to achieve superior business performance, it is recommended that entrepreneurs should focus on the cultivation and refinement of their entrepreneurial culture.